PENGEMBANGAN MODUL PEMBELAJARAN BIOLOGI DENGAN PENDEKATAN CONSTEXTUAL TEACHING AND LEARNING (CTL) YANG DILENGKAPI PETA KONSEP UNTUK SMA KELAS XI - Fitri, Ryantika; Sumarmin, Ramadhan; advinda, linda (Kolaboratif, 2015)
One aspect in learning that is related with the quality of learning is the availability of materials for students in learning process that assist students learning material independently. One of materials which can help students lead to independence learning is module. Through module, students can learn based on their own ability in learning. Module can be used for biology lesson. To facilitate students in understanding the biology lesson which is rich in concept, it takes an approach that focuses on emphasizing the learning concepts, and can apply in daily activity namely CTL approach map concept. The result of study is description of the CTL approach biology lesson modules equipped with map concept for 11th grade of Senior High School at the human regulatory system and human reproduction system material. Â